Adiposity and coronary heart disease in the UK Biobank: a prospective cohort study of 500 000 adults - Malden, DE (2020)
Background Excess adiposity is a known risk factor for coronary heart disease (CHD). However, the underlying mechanisms have not been fully elucidated, and the relevance of different adiposity phenotypes remains unclear.